Incident psychotic experiences following self‐reported use of high‐potency cannabis: Results from a longitudinal cohort study. - Hines, Lindsey A.; Heron, Jon; Zammit, Stanley (Addiction, 2024)
Background and aims: High‐potency cannabis has been associated with increased risk of psychosis, but a lack of prospective data hinders understanding of causality in this relationship. This study aimed to combine prospective report of cannabis use with retrospective report of potency to infer the potency of cannabis used in adolescence and explore whether use of cannabis, and the use of high‐potency cannabis, in adolescence is associated with incident psychotic experiences. Design: Population‐based birth cohort study. Setting: United Kingdom. Participants: n = 5570 participants who reported on any cannabis use (yes/no) age 16 and 18 years, and n = 1560 participants from this group who also retrospectively reported on cannabis potency. Measurements In questionnaires at ages 16 and 18, individuals self‐reported lifetime cannabis use, and at age 24, participants reported the type of cannabis they most commonly used in the whole time since first using cannabis. Psychotic experiences were assessed at age 24 years using the semi‐structured Psychosis‐Like Symptom Interview, with incident defined as new‐onset occurring between ages 19 and 24 years. Findings Use of high‐potency cannabis at age 16 or 18 was associated with twice the likelihood of experiencing incident psychotic experiences from age 19–24 (Odds Ratio 2.15, 95% Confidence Intervals 1.13–4.06). There was less evidence for an effect of any cannabis use on incident psychotic experiences (Odds Ratio 1.45, 95% Confidence Intervals 0.94–2.12). Conclusions: Use of high‐potency cannabis appears to be associated with increased likelihood of psychotic experiences.